Differential display - edited by R.A. Leslie; H.A. Robertson (Oxford University Press, 2000)
This book offers practical advice to researchers interested in using the technique of RT-PCR differential display to help them understand the function of individual genes in specific tissues or cells of an organism, either as part of normal development and aging, or in disease processes